Media Promosi Desa Wisata dalam Meningkatkan Kunjungan Wisatawan di Desa Golo Loni, Kecamatan Ranamese, Kabupaten Manggarai Timur, NTT - Anugrah, Dwi Tias; Setia, Hilaria Ichaina; Tamima, Zakia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
One of the tourism destinations in the NTT Province's East Manggarai Regency is Golo Loni Village. Finding out which promotional materials the Golo Loni tourist village uses to get more visitors was the aim of this study. A qualitative technique is the research methodology employed. methods for gathering data on the research topic through observations, literature reviews, and interviewing approaches. The study's findings indicated that the Golo Loni tourist village used print and digital advertising, including posters, brochures, websites, Facebook pages, Instagram accounts, and Youtube videos. It was able to draw tourists in thanks to promotions in these media. But the majority of the visitors were exclusively from within the country.